Plasticity and brittleness of the ordered βo phase in a TNM-TiAl alloy. (December 2022) - Molénat, Guy; Galy, Benjamin; Musi, Michael; Toualbi, Louïse; Thomas, Marc; Clemens, Helmut; Monchoux, Jean-Philippe; Couret, Alain
Abstract: In order to identify the reasons for the brittleness of a TNM-TiAl alloy (Ti51.05 Al43.9 Nb4 Mo0.95 B0.1 in at.%), the plastic deformation behaviour of the ordered βo phase is investigated. The corresponding powder was densified by Spark Plasma Sintering to produce a near lamellar microstructure made of γ/α2 lamellar colonies surrounded by γ and βo grains. Then, the room temperature tensile behaviour is studied by carrying out tensile tests and additional in-situ straining experiments in a transmission electron microscope (TEM). The TNM alloy exhibits a limited ductility, with the fracture surface of test specimens showing cleavage facets along lamellar interfaces. In addition, the βo grains contain nano-precipitates of the ωo phase and deform plastically by <111> superdislocations dissociated into two superpartial dislocations separated by an antiphase boundary. These dislocations glide in {011} planes and are observed to be localized into pile-ups, which is related to the ωo strengthening precipitation within the βo grains. This localised hardening behaviour leads to stress concentration in grain boundaries which is assumed to be responsible for delamination along lamellar interfaces in neighbouring lamellar colonies. Highlights: Role of the βo phase in the plasticity of the RT poorly ductile TNM-TiAl alloys. βo grains deform plastically by dissociated <111> superdislocations. Dislocations glide in {011} planes and tend to be localized into pile-ups. This localization is the result of the ωo precipitation that harden the βo grains. The corresponding stress concentration induce fracture along lamellae interfaces.